Pengembangan Program Pendidikan Anak Usia Dini (PAUD): Peran Pemberdayaan Kesejahteraan Keluarga Dalam Pos PAUD - J.M Tedjawati (Jurnal Pendidikan dan Kebudayaan, 2010)
The purpose of this research is to find informataion and data about: 1) Post implementation of the Post Early Childhood Education (Pos PAUD) in the community environment that includes characteristics of students, teachers, and administrators, the process of activities, evaluation and coaching; 2) PKK role in post implementation of the Post ECE; and 3) Obstacles and problems faced in the implementation of ECE services and attempt what can be done to overcome them. The methodology used is qualitative research, with the scope of this research is the implementation of ECE programs and the role of PKK Limapuluh Koto district, Gorontalo district, and Gowa district. The result showed that: 1) Post implementation of the region have implemented ECE integrated with IHC (Posyandu) and BKB activities; 2) the PKK has been carrying out its duties in cooperation with IHC (Posyandu)/ PHC (Puskesmas) and BKB, according to the ECE directorate hopes to help early childhood development, and 3) Obstacles found from the implementation of ECE, among others: (a) Lack of cadres and low educational cadres held; (b) Lack of mastery of the science education of the cadres held; (c) Lack of funds for the purchase of APE; (d) Limitations of space for games; and (e) Evaluation in ECE (PAUD) Programs. To minimalis of the obstaclce has been done by: 1) moving class; 2) using symple educational facilities with reuseable material; and 3) giving opportunity to the ECE cader to continue studying or following ECE training programe.Â ABSTRAKTujuan penelitian ini dimaksudkan untuk memperoleh data dan informasi tentang: 1) penyelenggaraan Pos PAUD di lingkungan masyarakat; 2) peran PKK dalam penyelenggaraan Pos PAUD; dan 3) hambatan dan upaya yang dilakukan. Metodologi yang digunakan adalah penelitian kualitataif, dengan lingkup penelitian pelaksanaan program Pos PAUD dan peran PKK di Kabupaten Limapuluh Koto, Kabupaten Gorontalo, dan Kabupaten Gowa. Hasil penelitian menunjukkan bahwa: 1) Pelaksanaan Pos PAUD di tiga kabupaten sudah diselenggarakan berintegrasi dengan kegiatan Posyandu dan BKB; 2) PKK telah bekerjasama dengan Posyandu/Puskesmas dan BKB sesuai dengan harapan Direktorat PAUD dalam menumbuh kembangkan anak usia dini; dan 3) Hambatan yang ditemukan antara lain masih terbatasnya: (a) tenaga kader dan masih rendahnya pendidikan kader, (b) penguasaan ilmu pendidikan para kader, (c) dana untuk pembelian alat permainan (PAUD), (c) ruang untuk bermain, dan (d) evaluasi program PAUD. Upaya yang dilakukan antara lain dengan cara: 1) menggunakan tempat kegiatan secara bergiliran; 2) menggunakan alat bantu mengajar dengan bahan sederhana; dan 3) memberikan kesempatan pada kader PAUD untuk mengikuti pelatihan PAUD.